Forecast of Impacts of Climate Change on Hydropower Potential of Ouémé River at the 2040's Horizon in Benin - NOUNANGNONHOU, Cossi Télesphore; FIFATIN, François-Xavier; Aza-Gnandji, Maurel Richy; ACAKPOVI, Amevi; SANYA, Emile (My University, 2018)
Abstract: Water is the most essential element for hydropower energy production. However, it has been well established that climate change will negatively globally impact water resources and in Sub-Saharan Africa particularly. It is therefore important to take this into account when assessing the potential hydropower energy of rivers to avoid overestimating their production’s capacity. This article firstly deals with the impacts of climate change on the forecast of potential hydropower energy of the Ouémé River Basin by 2040 and secondly develops the best equations for its exploitation. The data collected on three representative sites of the Ouémé River Basin (Bétérou, Savè, Kétou) from 1989 to 2016 and those derived from simulation of its flows from 2017 to 2040 by the Rural Engineering model (GR2M), made it possible to determine, first the monthly mean flow and, with the classified flow rate method, then evaluate the associated operating times. Using the obtained two parameters (mean flow-rate, production’s time), the hydropower energy was estimated as well, for period of 1989 to 2016, as for that of 2017 to 2040, and this in each of the retained three sites. The results show that the exploitable nominal flow-rates by hydroelectrical equipment set that can be installed are respectively 50 m3/s at Bétérou, 90 m3/s at Savè and 145 m3/s at Kétou. These results showed Kétou as the best site capable of hosting the largest hydropower energy plant on the Ouémé river basin. In Bétérou and Savè, the two-machines option (respectively 25 m3/s and 45 m3/s) is the most profitable, in terms of potential hydropower energy and its production duration, whereas in Kétou, the three-machines option of 50 m3/s each is the best.
Keywords: Forecast; GR2M; Climate Change; Ouémé River; Simulation; Hydropower Energy